Lesson Study Kaitannya dengan Peningkatan Kompetensi dalam Pembelajaran - Komarudin A; Moh. Abdul Qohar; Sholahudin Al Ayubi (Universitas Islam Jember, 2023)
Improving the quality of learning needs to be improved in an effort to improve the quality of education in Indonesia. Educators, in this case, teachers and lecturers, need to design learning so that the intended competencies can be achieved optimally. In addition, educators must also be able to evaluate themselves in an effort to improve the learning process that has been carried out. The purpose of this study is to describe lesson study in relation to increasing competence in learning. The research method used is a qualitative descriptive method, namely collecting library data from various sources, reading, recording, and processing research materials. The results of the study stated that lesson study as a form of fostering an educator in learning can collaborate with models, methods, strategies, and approaches and can be used as a benchmark for the learning process that has been carried out. Competence in this case relates to individual behavior consisting of affective, cognitive, and psychomotor Keywords: lesson study, learning competence